Penerapan Sistem Informasi Perpustakaan pada SMA Negeri 2 Muara Bungo Menggunakan Bahasa Pemrograman Java dan Mariadb - Yeviki Maisyah Putra (INTECOMS: Journal of Information Technology and Computer Science, 2018)
Computers are an electronic device that is not strange to every human being because it serves as a tool in all things. The computer has an application program capable of processing various types of data quickly, precisely and accurately. Therefore, many agencies that use computer services as a tool that can help in the activities of the company. Based on the research that has been done in the Library of SMA Negeri 2 Muara Bungo by using field research methods, libraries and laboratories, it is known that the system used in borrowing and returning books is still done manually and simply. With the design of Library information systems supported by Java programming language will provide better solutions to the problems encountered. The level of error in doing the calculations can be minimized, the information produced more accurately and the data can be stored safely. Keywords : Library, Java, MariaDB, Library Information System